Investigation of the impact of baffled-chute and divergence sidewall on the downstream scour pattern - Morteza Karimi Chahartaghi (Elsevier, 2021)
The effect of width opening downstream of chute structure on the depth and the dimensions of downstream scour hole was investigated using a physical model in the presence of two different block geometries, including a USBR block and a lattice block installed on chute. For this purpose, five chute structures with baffled blocks were designed and constructed, including three models with a divergence ratio of 1.45, 1.75, and 2.45, including a USBR block and 2 models without divergence with a divergence ratio of 1, including USBR and lattice blocks. The results increase the chute widening ratio from 1 to 2.45 reduced the mean and maximum depths and the mean and maximum lengths of scour pit, while enhancing the flow energy dissipation along the chute. Besides, using perforated piers increased the length of scour pit, while reducing its depth and the relative flow energy dissipation.